Bridging the gap: gender-specific preferences in STEM occupations in vocational education and training - Tamara Gutfleisch; Richard Nennstiel (Empirical Research in Vocational Education and Training)
Abstract Women’s underrepresentation in science, technology, engineering, and mathematics (STEM) has been widely studied, particularly in the context of general and tertiary education. However, less is known about gendered STEM sorting within vocational education and training (VET), despite VET systems playing a key role in occupational gender segregation. This study investigates gender differences in the likelihood of choosing a STEM occupation in VET using nationally representative data from Switzerland. We examine to what extent commonly studied individual-level mechanisms—such as math achievement, math self-concept, and career values—can explain the gender gap in STEM participation. To assess whether these mechanisms operate similarly across educational pathways and outcome types, we compare students pursuing or intending to pursue VET to those aspiring to an academic degree, and examine three STEM-related outcomes: intended VET occupation, aspirations for a STEM job at age 30, and intentions to pursue a math-intensive job. We find that the gender gap in STEM participation is largest in VET occupations and considerably smaller for the other two outcomes. Moreover, a larger share of the gender gap can be explained regarding occupational aspirations as opposed to VET occupations, and among students aspiring to academic education. These findings suggest that theoretical models of STEM sorting should be adapted to better reflect the specific features of VET and the types of occupations it comprises.